Caracterización y optimización del proceso de extracción de pectina a partir del fruto de anihuayo Plinia clausa Mc Vaugh. - Romero Piña, Silvia Shantal (2024)
The research has a quantitative experimental orientation, its objective was to determine the optimal parameters for the extraction of pectin by acid hydrolysis and alcohol precipitation from the fruits of the anihuayo Plinia clausa Mc Vaugh, The study population consisted of all the fruits of anihuayo, which are sold in the Belén market in the district of Iquitos in the province of Maynas, Loreto Region; a non-random sampling was carried out at the discretion of the authors, the sample size was 5 kg of ripe fruits. For the extraction was used citric acid at pH: 1.5, 2.5 and 3.5 and times of: 45, 60, and 75 minutes, for temperatures of: 60, 75 and 80ºC, a factorial design 23 was used. This design showed that the pH and time have statistical significance, while the temperature did not show to have significant effect, so the adjustment was made to the factorial design 22 with respect to pH and time, finding that the highest yield to the adjusted design was of 16.5% of pectin (pH 1.5 and time 75 minutes). To determine the quality, a physicochemical characterization of the pectin was carried out, classifying it as high methoxyl pectin. In conclusion, it is established that the optimum parameters for obtaining the highest yield of pectin from the fruits of anihuayo Plinia clausa Mc Vaugh. By means of acid hydrolysis are pH 1.5 and time 75 minutes.